ANALISIS BERPIKIR KREATIF DALAM MENYELESAIKAN MASALAH BARISAN DAN DERET ARITMATIKA DENGAN METODE OPEN-ENDED - Darminto, Bambang Priyo; Setianingsih, Lilis (Universitas Muhammadiyah Purworejo, 2019)
This study aims to determine students creative thinking skills in solving arithmetic progression and series problems with the open-ended method. The research method used is a qualitative method with a case study approach. The selection of subjects uses a purposive technique that is based on certain characteristics. The subjects in this study were 3 junior high school students selected in the category of high matematical abilities. Methods of collecting data using tests, interviews, field notes, and documentation. Data analysis techniques used the triangulation method to gain deeper understanding of the subject under study. Based on the results of the study show the ability of creative thinking of students because it meets the three indicators of creative thinking, namely fluency: students are able to calculate smoothly and solve problems correctly, flexibility: students are able to find other ways to find the same results, novelty: students are able to think in new ways and different from other subjects.